Retrospective Descriptive Study Overview Causes Of Patients With Spinal Cord Injury To The Inpatients At Melati Hospital, Sungai Penuh City In 2021 - Mei Sandra, Ferdian (Talenta Universitas Sumatera Utara, 2022)
Spinal Cord Injury is all injuries to the spinal cord which can cause motor and sensory disturbance and even cause permanent disability and death. This study aims to determine the description of the causes of patients with Spinal Cord Injury. This type of research is retrospective descriptive. Using cross sectional techniques in sampling, the number of samples is 21 medical records of patients with a diagnosis of Spinal Cord Injury, The instruments in this study used the Spinal Cord Injury checklist sheet, while the observed variables were: causal factors and Spinal Cord Injury. The results of the study are as follows: 71.43% of the respondents' gender is male, 61.9% of the respondent's age are old age, 33.33% of the respondents' education is elementary school, and 38.1% of the respondents' occupations are entrepreneurs. The cause of Spinal Cord Injury 71.43% is traumatic, with most cases falling from a height of 53.33% , non-traumatic causes as many as 28.67% with the most cases are infections. The most common Spinal Cord Injury classifications are Grade E 52.37% and Grade A 19.5%. Incomplete lesions as much as 66.67% with symptoms of impaired mobilization as much as 66.67%. The most common cause of Spinal Cord Injury is can be concluded that the most common cause is TSCI / Traumatic Spinal Cord Injury with the highest prevalence is falling from height